If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y(y + -7) + -4(y + -7) = 0 Reorder the terms: 3y(-7 + y) + -4(y + -7) = 0 (-7 * 3y + y * 3y) + -4(y + -7) = 0 (-21y + 3y2) + -4(y + -7) = 0 Reorder the terms: -21y + 3y2 + -4(-7 + y) = 0 -21y + 3y2 + (-7 * -4 + y * -4) = 0 -21y + 3y2 + (28 + -4y) = 0 Reorder the terms: 28 + -21y + -4y + 3y2 = 0 Combine like terms: -21y + -4y = -25y 28 + -25y + 3y2 = 0 Solving 28 + -25y + 3y2 = 0 Solving for variable 'y'. Factor a trinomial. (4 + -3y)(7 + -1y) = 0Subproblem 1
Set the factor '(4 + -3y)' equal to zero and attempt to solve: Simplifying 4 + -3y = 0 Solving 4 + -3y = 0 Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -3y = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -3y = 0 + -4 -3y = 0 + -4 Combine like terms: 0 + -4 = -4 -3y = -4 Divide each side by '-3'. y = 1.333333333 Simplifying y = 1.333333333Subproblem 2
Set the factor '(7 + -1y)' equal to zero and attempt to solve: Simplifying 7 + -1y = 0 Solving 7 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1y = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1y = 0 + -7 -1y = 0 + -7 Combine like terms: 0 + -7 = -7 -1y = -7 Divide each side by '-1'. y = 7 Simplifying y = 7Solution
y = {1.333333333, 7}
| -(x-4)+2=13 | | 4x^2-11x+8=6x+4 | | (6x-3)2=(4x+7)3 | | 3x=5(x-6) | | 27+u=3-3u | | 2(5+x)=150 | | 7-1x=4+x | | x^4-9x^3+27x^2-15x-52=0 | | X=45-4x | | 7-x+2=2x-12 | | 9x^2+17=71 | | 0=8t | | -x^2+9x=18 | | 6x^2-12x=-1 | | -7x=2x+3 | | 3m-2=-5m+9 | | x-8.8=-6.9 | | -6x+24=18 | | 15X+100000=14x+200000 | | 2b+6a=14 | | 4(x)-24=-20 | | 3(x-3)=-6 | | -x^2+11x=18 | | 3a+4b-5c=0 | | 4k^2+12k+9=0 | | -5x+17=-2x-4 | | p+31=13 | | 9v-5v=44 | | 3x-3=100 | | -2x+24=14 | | x+23=-14 | | -3x+1=-6x+2 |